Application of the Triple Exponential Smoothing Method in Forecasting Covid-19 Cases in Central Java - Noor Sofiyati; Ambar Winarni (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Currently, Covid-19 cases are decreasing, but it can still pose a threat to the people of Indonesia, not least for the people in Central Java Province, with a reasonably dense population and high mobility. In the future, Covid-19 cases may increase again, so forecasting is needed to predict Covid-19 cases as consideration for a better policy for the government, education authorities, and the Health Office of Central Java in 2023. This research aims to determine the development of Covid-19 cases in Central Java by conducting simulations using the Triple Exponential Smoothing Winter (TESW) forecasting method. This method was used because the data of Covid-19 cases in Central Java fluctuated randomly, and there was a seasonal effect. There are two seasonal models in the Triple Exponential Smoothing Winter method: the additive model and the multiplicative model. Based on the research results, the Triple Exponential Smoothing Winter multiplicative model was better than the additive model indicated by a smaller MAPE value of 15.69% for forecasting the number of Covid-19 cases in Central Java from May 2022 to December 2022. Forecasting result shows that Covid-19 cases are gradually decreasing every month.